Cochlear Implantation in Children with Single‐Sided Deafness. (17th February 2020) - Deep, Nicholas L.; Gordon, Steven A.; Shapiro, William H.; Waltzman, Susan B.; Roland, J. Thomas; Friedmann, David R.
Abstract : Objective: To describe our experience with children undergoing unilateral cochlear implantation (CI) for treatment of single‐sided deafness (SSD). Study Design: Retrospective case series. Methods: A retrospective case review from a tertiary referral center involving 14 pediatric patients (<18 years) with SSD who underwent unilateral CI. Speech perception testing in quiet and noise in the CI‐only and bimodal conditions with at least 1 year of device use and device usage from data logs represent the main outcome measures. Results: The mean age at CI was 5.0 years (median 4.4, range 1.0–11.8 years). The mean duration of deafness was 3.0 years (median 2.4, range 0.6–7.0 years). Mean follow‐up was 3.4 years. Speech perception testing with a minimum of 1 year post‐CI was available in eight patients. The mean word recognition scores (WRS) in the CI‐only condition was 56%; a significant improvement from baseline. Testing in background noise with spatially separated speech and noise revealed that patients scored as well or better with the CI‐on versus CI‐off in all conditions and in no cases was interference from the CI noted. Data logs were reviewed for device usage which revealed an average use of 6.5 hr/d. Conclusion: Cochlear implantation is a viable treatment option for pediatric SSD in this self‐selected cohort. Open‐set speech and improvement in background noise can be achieved. Careful patient selection and thorough counseling on expectations is paramount to achieving successful outcomes. Level of Evidence: IV Laryngoscope, 131:E271–E277, 2021